Parsimonious Mixed Bergomi Models for VIX Derivatives: Calibration and Estimation via Quantization - Kyakutwika, Nelson (Stellenbosch : Stellenbosch University, 2026)
Thesis (PhD)--Stellenbosch University, 2026.